Temporality and space in highly skilled migrants' experiences of education and work in the rural north of Sweden. Issue 5 (2nd November 2021) - Carlbaum, Sara
ABSTRACT: The aim of this article is to critically explore and analyse opportunities and obstacles faced by highly skilled migrants in rural areas seeking to re-enter their profession, focusing on the lived experiences of migrants residing in northern Sweden. Analysis of their stories focusing on intersections of temporal and spatial positionings reveal different lived experiences and opportunities depending on migration regime and policy, gender, age and family situation, profession and labour market needs. However, similar challenges also emerged related to rurality such as rural dismantling and poverty of access to (and support for) both adult education generally and specific fast tracks for highly skilled migrants, with accompanying risks of deskilling and marginalisation. The stories also indicate that the rural idyll tends to provide closer social networks than those in cities, thereby increasing opportunities for re-entry to former professions. However, workfare policies and devaluation of foreign credentials lead to requirements for re-education to re-enter former professions or undertake other work (high- or low-level) that are particularly difficult to meet in rural settings.